Conservation options for Blouberg, Lebowa : proposals based on a socio-ecological study - Ferguson, C C (Christopher Charles) (Department of Environmental and Geographical Science, 2024)
The Blouberg mountain range, in the north-western area of Lebowa, is culturally significant as the traditional royal headquarters of the Bahananwa tribe, and ecologically unique because of the endemic flora located on its slopes. The communities occupying the upper plateaux have remained isolated from the influences of modern development because of the absence of roads. Access is limited to steep and rugged mountain paths'. The inhabitants of the mountain have largely lived in harmony with their environment, but a large and growing population around the base of Blouberg is placing stress upon the natural resource base. As a result, research was initiated in order to develop a range of conservation strategy options which would meet the goals of ensuring the sustainability of the natural resources of the area and enhancing the lifestyles of the local inhabitants. The research procedure adopted consisted of the gathering of secondary data, a social survey, bio-physical survey and panel evaluations. Secondary data was gathered from a wide range of sources and included interviews with individuals and a computer-aided library search. A social survey was conducted amongst inhabitants of the mountain plateaux and locals living around the base of the mountain in order to determine the basic needs, aspirations and attitudes of the communities. The biophysical survey revealed areas where environmental degradation had occurred and was occurring. Threats to the natural resource base were also identified. An information document, comprising information compiled during the first three phases of the research was circulated to individuals who had been approached to participate in two workshops convened by the researcher. The purpose of these workshops was to identify environmental characteristics of Blouberg worthy of ii conservation, identify hazards to these, establish means to counteract them and suggest specific conservation principles which should be incorporated in conservation strategy options. Six conservation strategy options which were formulated as a result of the research procedure described above, are presented by the researcher. In the final analysis recommendations as to the choice and implementation of one of the options is proposed. The advantages of this approach are that a thorough investigation of opinions and alternatives should lead to the implementation of the most viable, equitable and sustainable conservation strategy for Blouberg.